Positive Emotion Facilitates Audiovisual Binding - Kitamura, Miho S.; Watanabe, Katsumi; Kitagawa, Norimichi (Frontiers in Integrative Neuroscience, 2016)
It has been shown that positive emotions can facilitate integrative and associative information processing in cognitive functions. The present study examined whether emotions in observers can also enhance perceptual integrative processes. We tested 125 participants in total for revealing the effects of emotional states and traits in observers on the multisensory binding between auditory and visual signals. Participants in Experiment 1 observed two identical visual disks moving toward each other, coinciding, and moving away, presented with a brief sound. We found that for participants with lower depressive tendency, induced happy moods increased the width of the temporal binding window of the sound-induced bounce percept in the stream/bounce display, while no effect was found for the participants with higher depressive tendency. In contrast, no effect of mood was observed for a simple audiovisual simultaneity discrimination task in Experiment 2. These results provide the first empirical evidence of a dependency of multisensory binding upon emotional states and traits, revealing that positive emotions can facilitate the multisensory binding processes at a perceptual level.